A history of communication technology - Loubere, Philip A. (New York, NY : Routledge, 2021)
"This book is a comprehensive illustrated account of the technologies and inventions in mass communication that have accelerated the advancement of human culture and society. A History of Communication Technology covers a timeline in the history of mass communication that begins with human prehistory and extends all the way to the current digital age. Using rich, full-color graphics and diagrams, the book details the workings of various mass communication inventions, from paper-making, printing presses, photography, radio, TV, film and video, to computers, digital devices and the Internet. Readers are given insightful narratives on the social impact of these technologies, brief historical accounts of the inventors, and sidebars on the related technologies that enabled these inventions. This book is ideal for students in introductory mass communication, visual communication, and history of media courses, offering a highly approachable, graphic-oriented approach to the history of communication technologies"--
OCLC-licensed vendor bibliographic record.
Keywords: Communication and technology -- History; Communication -- Technological innovations -- History; Telecommunication -- History; Digital communications -- History; Current events -- Psych; LANGUAGE ARTS & DISCIPLINES / Communication